More than Pneumonia: Distinctive Features of SARS-Cov-2 Infection. From Autopsy Findings to Clinical Implications: A Systematic Review - Stefano D’Errico (Microorganisms, 2020)
Despite safety recommendations for the management of corpses with COVID-19 infection and the high number of deaths worldwide, the post-mortem investigation rate is extremely low as well as the scientific contributions describing the pathological features. The first results of post-mortem investigations provided interesting findings and contributed to promoting unexplored therapeutic approaches and new frontiers of research. A systematic review is provided with the aim of summarizing all autopsy studies up to February 2020 in which a complete post-mortem investigation in patients with COVID-19 disease was performed, focusing on histopathological features. We included case reports, case series, retrospective and prospective studies, letters to the editor, and reviews. A total of 28 studies fulfilled the inclusion criteria, producing a pooled dataset of 407 full autopsies. Analyzing the medical history data, only 12 subjects had died without any comorbidities (for 15 cases the data were not available). The post-mortem investigation highlighted that acute respiratory distress syndrome (ARDS) and multiple organ failure represent the main clinical features of COVID-19 disease, often leading to pulmonary thromboembolism and superimposed bronchopneumonia. The discussed data showed a strict relationship among the inflammatory processes, diffuse alveolar, and endothelial damage. In light of these results, the full autopsy can be considered as the gold standard to investigate unknown infections or pathogens resulting in death.